2015
DOI: 10.1016/j.jmpt.2013.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Serious Adverse Events and Spinal Manipulative Therapy of the Low Back Region: A Systematic Review of Cases

Abstract: Objective: To systematically search the literature for studies reporting serious adverse events following lumbopelvic spinal manipulative therapy (SMT) and to describe the case details. Methods:A systematic search was conducted in PubMed including MEDLINE, EMBASE, CINAHL and The Cochrane Library up to January 12, 2012 by an experienced reference librarian. Study selection was performed by 2 independent reviewers using predefined criteria.We included cases involving individuals 18 years or older who experienced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
39
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(42 citation statements)
references
References 73 publications
0
39
0
2
Order By: Relevance
“…A 2013 systematic review of serious adverse events following SM found cases of cauda equina syndrome (38%); lumbar disk herniation (30%); fracture (9%); and formation of hematoma or hemorrhagic cyst (8%). 25 A 2012 literature review of accidents associated with cervical SM over a 32 year period in China found cases of cord injury or compression, nerve root injury, cervical spine dislocation, and soft tissue injury. 26 This report may have overestimated the risks of SM performed by a licensed chiropractor however, because the practice of chiropractic in China is unrecognized and unregulated.…”
Section: Introductionmentioning
confidence: 99%
“…A 2013 systematic review of serious adverse events following SM found cases of cauda equina syndrome (38%); lumbar disk herniation (30%); fracture (9%); and formation of hematoma or hemorrhagic cyst (8%). 25 A 2012 literature review of accidents associated with cervical SM over a 32 year period in China found cases of cord injury or compression, nerve root injury, cervical spine dislocation, and soft tissue injury. 26 This report may have overestimated the risks of SM performed by a licensed chiropractor however, because the practice of chiropractic in China is unrecognized and unregulated.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, SMT creates significant changes in spinal stiffness, muscle response and disc diffusion in SMT responders while these same changes are not observed in SMT non-responders234. In addition, approximately 30–50% of persons who receive SMT experience some kind of benign adverse event that typically self-resolves in 24–48 hours567, with a minority of patients experiencing serious adverse events8910. However, causation in these cases remains controversial79101112.…”
mentioning
confidence: 99%
“…Some of these reviews further specified SMT as cervical, thoracic or lumbar SMT (21 reviews [46, 47, 49, 54, 57, 65, 91, 96, 103, 105, 114, 115, 119, 121, 123, 125127, 134, 136, 150]). Other reviews did not further specify than ‘manipulation’ (10 reviews [36, 66, 7073, 79, 93, 101, 107]), ‘osteopathic manipulative treatment/therapy’ (8 reviews [38, 52, 56, 64, 81, 82, 116, 139]), and ‘chiropractic care/interventions’ (5 reviews [67, 98100, 137]).…”
Section: Resultsmentioning
confidence: 99%